Not Enough to Memorize but Preserve Memory of the Quran: A Grounded Theory Study - Siti Mujijatirrahmah; Zamili, Moh. (Jurnal Pendidikan Islam Indonesia, 2025)
The inability to preserve the memorization of the Quran is a threat to the huffadz in pesantren. Variants of memorization methods do not guarantee the preservation of memorization in the long term. The historical roots that preserve the memorization of the Quran have been recorded since the 6th century, becoming a tradition in the 17th century in Malay culture, then growing within the scope of pesantren in the early 19th century until now. This research aims to analyze and answer the above problems entitled prototype of a’rif al-haqiqqah, al qira’ah bibath’, tashih al-qira’ah (called HBTQ). A comprehensive study was explored using a grounded theory strategy through the Charmaz constructivist approach to construct the HBTQ prototype as a strategy for preserving Quran memorization Ma’had Qur’an Putri Pondok Pesantren Salafiyah Syafi’iyah Sukorejo. The research results show that this strategy ensures that every procedure is guaranteed accurate but sweetened with embedded transcendental factors such as setting targets, making a daily schedule, memorizing with tajwid-coded mushaf, having tashih al-tilawah friends, and forming habits al-qira’ah bibath’.